Development of a Murine Infection Model with Leishmania killicki, Responsible for Cutaneous Leishmaniosis in Algeria: Application in Pharmacology - Eddaikra, Naouel (Biomed Res Int, 2016)
In Algeria, Leishmania infantum, Leishmania major, and Leishmania killicki (Leishmania tropica) are responsible for cutaneous leishmaniosis. We established a murine model of L. killicki infection to investigate its infective capacity, some immunophysiopathological aspects, and its suitability for pharmacological purposes. Following the injection of L. major or L. killicki metacyclic promastigotes in the ear dermis of BALB/c mice, the course of infection was followed. The infection with L. killicki caused slower lesion formation than with L. major. The presence of L. killicki or L. major DNA and parasites was detected in the ear dermis and in lymph nodes, spleen, and liver. Lesions induced by L. killicki were nonulcerative in their aspect, whereas those caused by L. major were highly ulcerative and necrotic, which matches well with the lesion phenotype reported in humans for L. killicki and L. major, respectively. The treatment of L. killicki lesions by injection of Glucantime® significantly reduced the lesion thickness and parasite burden. Ear dermal injection of BALB/c mice constitutes a model to study lesions physiopathology caused by L. killicki and presents interest for in vivo screening of new compounds against this pathogen, emerging in Algeria.